A Conceptual Model for Assessing the Minimum Size Area for an Area-Wide Integrated Pest Management Program. (2nd March 2011) - Barclay, Hugh J.; Matlock, Robert; Gilchrist, Stuart; Suckling, David M.; Reyes, Jesus; Enkerlin, Walther R.; Vreysen, Marc J. B.
Abstract : A conceptual model was developed based on the two basic spatial elements of area-wide integrated pest management (AW-IPM), a core area and a buffer zone, to determine the minimum size of the protected area for the program to be technically feasible and economically justifiable. The model consisted of a biological part (insect dispersal) and an economic part. The biological part used random walks and diffusion equations to describe insect dispersal and to determine the minimum width of the buffer zone required to protect the core area from immigration of pests from outside. In the economic part, the size of the core area was calculated to determine the point at which the revenues from the core area equal the control costs. This model will need to be calibrated and validated for each species and geographic location. Tsetse flies and the Mediterranean fruit fly are used as case studies to illustrate the model.